Problems of Social Adjustment for Iraqi Students Immigrating to Egypt- A Field Study in the City of Cairo - - Abdel Aziz Omar, Ahmed Abdel Aziz (Journal of Tikrit University for Humanities, 2022)
The study attempts to expound the social adaptation problems encountering Iraqi student immigrating to the Egypt. The Egyptian society has witnessed the immigration of a large number of Iraqi students because of the encouraging facilities in the educational institutions especially towards students from Arab countries. This motivated a large number of Iraqi students that had not have a chance to pursue higher education opportunities in Iraq, thus, finding an alternative in Egypt. The researcher devised a social adaptation measure in order to achieve the objectives of the study. The measure included four topics that include the most encountered social, economic, cultural and health related difficulties that encounter the Iraqi students in Egypt. The measure was distributed among (200) male and female students in Cairo. From analyzing the result the researcher concluded the following main results: Iraqi student encounter social adaptively difficulties in the Egyptian society because (72.7 %) of the investigated students indicated that they have encountered social problems and (73.8%) of the students stated that they have encountered economic problems while (61.8%) responded by indicating that they suffer psychological difficulties. The researcher found that the female students were less adaptive than the male students in the Egyptian society. The younger category groups of Iraqi students are less adaptable than the older in the Egyptian society. The researcher found that the single Iraqi students were less adaptive than the married students in the Egyptian society. The researcher found that the unemployed Iraqi students were less adaptive than the employed students that have administrative jobs in their country.